2017
DOI: 10.3389/fnhum.2017.00353
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for Assessment of Gait and Reference Values for Spatiotemporal Gait Parameters in Older Adults: The Biomathics and Canadian Gait Consortiums Initiative

Abstract: Background: Gait disorders, a highly prevalent condition in older adults, are associated with several adverse health consequences. Gait analysis allows qualitative and quantitative assessments of gait that improves the understanding of mechanisms of gait disorders and the choice of interventions. This manuscript aims (1) to give consensus guidance for clinical and spatiotemporal gait analysis based on the recorded footfalls in older adults aged 65 years and over, and (2) to provide reference values for spatiot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
109
3
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(121 citation statements)
references
References 59 publications
8
109
3
1
Order By: Relevance
“…Ambulatory activity for these mostly octogenarians was high, with similar values for all participants apart from one highly active individual, who walked on average over 18,000 steps a day, and was active for 237 minutes of the day. Participants walked with an average gait speed of 1.01 ms -1 which is comparable to age-referenced data (Beauchet et al, 2017). TUG single task scores were comparable to those reported for non-fallers (Weiss et al, 2013), although balance confidence scores were considerably higher (80% compared with 53% confidence).…”
Section: Resultssupporting
confidence: 68%
“…Ambulatory activity for these mostly octogenarians was high, with similar values for all participants apart from one highly active individual, who walked on average over 18,000 steps a day, and was active for 237 minutes of the day. Participants walked with an average gait speed of 1.01 ms -1 which is comparable to age-referenced data (Beauchet et al, 2017). TUG single task scores were comparable to those reported for non-fallers (Weiss et al, 2013), although balance confidence scores were considerably higher (80% compared with 53% confidence).…”
Section: Resultssupporting
confidence: 68%
“…However, even if we used 3 steps for acceleration/deceleration phases that were in average shorter than 2 m, we believe this was not a major methodological limitation of this study. Indeed, more recent guidelines for the assessment of gait in older adults from the Biomathics and Canadian Gait Consortiums Initiative reported that a steady-state gait can be achieved by instructing participants to start walking 1 m prior to the data recording zone and stopping at least 1 m beyond it 39 . Moreover, other studies have suggested that the transition of the body to steady gait pattern occurs rapidly over a period that can range from one 40 to three steps 41 and that measures of gait variability measured on a shorter walkway with shorter acceleration/deceleration phases (i.e., 4-m walkway plus 1-m for acceleration and deceleration phases) showed: (1) good test–retest reliability and concurrent validity, as indicated by associations with functional status and poorer health 42 ; (2) associations with history of falls in the past year 43 ; and (3) predictive ability for future mobility impairments and disability 44 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, cluster group 3 (lowest level) yielded similar GV and PCI ranges compared with the healthy elderly population evaluated in previous studies (our young adults vs. elderly adults in previous studies = stride length: 3.31% vs. 2.23%-2.42%, single support phase: 6.24% vs. 3.90%-6.00%, double support phase: 12.16% vs. 6.00%-6.80%, and PCI: 4.11% vs. 3.30% to 6.10%) [1,6,10,13,49]. Increased PCI values imply poorer bilateral coordination that may be related to worsened gait coordination capacity and worsened dynamic stability [10][11][12][13].…”
Section: Discussionmentioning
confidence: 95%